Changes in the Spatial Distribution of the Level and Dynamics of Socio-Economic Development of Rural Areas in Poland - Monika Stanny; Andrzej Rosner; Edyta Kozdroń (Wieś i Rolnictwo)
Abstract: This article shows the characteristics of spatial differentiation of level and dynamics of socio-economic development of rural areas in Poland. The Authors try to define typical directions of the development of gminas and look for an answer to the question: what, and what gminas’ features, determine the direction of development? The analysis presented in the paper has been based on the data originating from the Rural Development Monitoring Project. The results showed the differentiation of the development level to be a part of very dynamic contemporary reality. Criteria up to this date documented in research and arranging spatial diversity of social and economic phenomena apply specifically to description of the development’s level, while dynamics is being arranged by a different criteria. Moreover, the research describes four basic profiles of the dynamics of gminas’ development.